Effects of Atorvastatin, Amlodipine, and Their Combination on Vascular Dysfunction in Insulin-Resistant Rats - Tomio Okamura; Masashi Tawa; Ayman Geddawy; Takashi Shimosato; Hirotaka Iwasaki; Haruo Shintaku; Yuichi Yoshida; Masahiro Masada; Kazuya Shinozaki; Takeshi Imamura (Elsevier, 2014)
Abstract.: Deficiency of tetrahydrobiopterin (BH4) in the vascular tissue contributes to endothelial dysfunction through reduced eNOS activity and increased superoxide anion (O2−) generation in the insulin-resistant state. We investigated the effects of atorvastatin, a 3-hydroxyl-3-methylglutaryl coenzyme A (HMG CoA) reductase inhibitor; amlodipine, a calcium antagonist; and their combination on blood pressure, arterial relaxation and contraction, and vascular oxidative stress in aortas of high fructose-fed rats. Oral administration of atorvastatin for 8 weeks did not significantly lower blood pressure, but normalized angiotensin II-induced vasoconstriction and endothelial function in the fructose-fed rats. Atorvastatin treatment of fructose-fed rats increased vascular BH4 content, which was associated with an increase in endothelial NO synthase activity as well as a reduction in endothelial O2− production. On the other hand, administration of amlodipine did not affect the angiotensin II-induced vasoconstriction and endothelial function, but normalized the elevated blood pressure in the fructose-fed rats. The combined treatment did not show synergistic but additive beneficial effects. The present study suggests that combined therapy of HMG-CoA reductase inhibitors and calcium antagonists prevents functional vascular disorders in the insulin-resistant state, possibly resulting in the protection against or delay of development of hypertension, vascular dysfunction in diabetes, and thereafter atherosclerosis. Keywords:: 3-hydroxyl-3-methylglutaryl coenzyme A reductase inhibitor, calcium antagonist, nitric oxide, tetrahydrobiopterin, insulin resistance